2013
DOI: 10.1111/sji.12075
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a Inhibits Human Monocyte‐Derived Myeloid Dendritic Cell Generation

Abstract: Wnt5a is a non-canonical Wnt protein that is expressed at elevated levels in inflammatory conditions. Its role in inflammation remains unclear, although it is known that Wnt5a is expressed at a higher level in monocyte-derived myeloid dendritic cells (Mo-mDCs) than in monocytes and macrophages. The function of Wnt5a in dendritic cells (DCs) remains relatively unexplored. Here, we found that under Mo-mDC culture conditions, Wnt5a inhibited the generation of CD14 +/low Mo-mDCs while promoting the generation of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
5
17
0
Order By: Relevance
“…rWNT5A also induced IL-6 secretion over a longer time period as measured by Elisa at 3 h, 6 h, 12 h, 24 h and 48 h (Figure 1C). We have previously shown that WNT5A induces IL-10 [27] and IL-6 [28] in human monocytes. In Mewo cells however, IL-10 was not even expressed at the mRNA level (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…rWNT5A also induced IL-6 secretion over a longer time period as measured by Elisa at 3 h, 6 h, 12 h, 24 h and 48 h (Figure 1C). We have previously shown that WNT5A induces IL-10 [27] and IL-6 [28] in human monocytes. In Mewo cells however, IL-10 was not even expressed at the mRNA level (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Mesenchymal glioblastomas have a higher probability of elevated expression of SPP1 than do other subtypes of glioblastoma, whereas classical glioblastomas are less likely to express SPP1 in glioblastoma-infiltrating innate immune cells. The role of WNT5A in modulation of the glioblastoma microenvironment has yet to be explored, but researchers have shown it to mediate monocyte accumulation in patients with cancer (58) and induce macrophage-related breast cancer cell invasion (59). Finally, several of the upregulated genes in CD14 + cells are directly implicated in clinical characteristics such as the extent of edema on magnetic resonance images (60).…”
Section: Discussionmentioning
confidence: 99%
“…However, neither WNT5A protein nor WNT5A mRNA expression were affected in the WM852 and the A2058 cell lines. In this context, it deserves to be mentioned that a reverse mechanism has been reported, in that WNT5A can increase the expression of IL‐6 both in vitro in monocytes (Bergenfelz et al., 2013) and in vivo in the spinal cord (Li et al., 2013). These findings might explain the observation by Dissanayake et al.…”
Section: Discussionmentioning
confidence: 99%